Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,414 questions

17,804 answers

1,438 comments

45,550 users

Perform the multiplication and use the fundamental identities to simplify.

0 votes

There is more than one correct form (tan x + sec x)(tan x - sec x)

asked Dec 26, 2017 in TRIGONOMETRY by anonymous

1 Answer

0 votes

(tan x + sec x)(tan x - sec x)   =   (tan^2 x - sec^2 x)

                                               =   -1 (- tan^2 x + sec^2 x)       [ (a + b)(a - b)  =  a^2 - b^2 ]

                                               =   -1 (sec^2 x - tan^2 x)

                                               =   -1 (1)                                  [ sec^2 x - tan^2 x  =  1 ]

(tan x + sec x)(tan x - sec x)   =  - 1 

answered Dec 26, 2017 by homeworkhelp Mentor

Related questions

...